An Endocrine-Disrupting Chemical, Bisphenol A Diglycidyl Ether (BADGE), Accelerates Neuritogenesis and Outgrowth of Cortical Neurons via the G-Protein-Coupled Estrogen Receptor - Ikuko Miyazaki; Chiharu Nishiyama; Takeru Nagoshi; Akane Miyako; Suzuka Ono; Ichika Misawa; Aika Isse; Kana Tomimoto; Kaori Masai; Kazumasa Zensho; Masato Asanuma (NeuroSci, 2025)
Bisphenol A diglycidyl ether (BADGE) is the main component of epoxy resin and is used for the inner coating of canned foods and plastic food containers. BADGE can easily migrate from containers and result in food contamination; the compound is known as an endocrine-disrupting chemical. We previously reported that maternal exposure to bisphenol A bis (2,3-dihydroxypropyl) ether (BADGE·2H2O), which is the most detected BADGE derivative not only in canned foods but also in human specimens, during gestation and lactation, could accelerate neuronal differentiation in the cortex of fetuses and induce anxiety-like behavior in juvenile mice. In this study, we investigated the effects of low-dose BADGE·2H2O (1–100 pM) treatment on neurites and the mechanism of neurite outgrowth in cortical neurons. BADGE·2H2O exposure significantly increased the number of dendrites and neurite length in cortical neurons; these accelerating effects were inhibited by estrogen receptor (ER) antagonist ICI 182,780 and G-protein-coupled estrogen receptor (GPER) antagonist G15. BADGE·2H2O down-regulated Hes1 expression, which is a transcriptional repressor, and increased levels of neuritogenic factor neurogenin-3 (Ngn3) in the cortical neurons; the changes were significantly blocked by G15. These data suggest that direct BADGE·2H2O exposure can accelerate neuritogenesis and outgrowth in cortical neurons through down-regulation of Hes1 and by increasing Ngn3 levels through ERs, particularly GPER.